Pathogenetic therapy of mitral valve prolapse - E. G. Malev; S. V. Reeva; M. Yu. Omelchenko; L. B. Mitrofanova; E. V. Timofeev; N. N. Parfenova; E. B. Luneva (Российский кардиологический журнал, 2025)
Aim. To evaluate the effect of angiotensin II receptor blocker (ARB) therapy on the expression of transforming growth factor-β (TGF-β) in the myxomatous mitral valve, on the serum levels of TGF-β1/TGF-β2 and the left ventricular (LV) systolic function in patients with mitral valve prolapse (MVP).Material and methods. The retrospective non-randomized single-center study included 233 patients who underwent surgical treatment of severe mitral regurgitation due to MVP. Preoperative drug therapy was assessed using case records. Transthoracic echocardiography was performed in all patients before surgery. Pathological and immunohistochemical analysis of mitral valve fragments removed during surgery were performed. The serum content of TGF-β1 and TGF-β2 was determined by the enzyme immunoassay.Results. According to echocardiography, mitral valve leaflets were significantly longer and thicker in patients in the control group than in the ARB group. These data were confirmed by pathological study — most patients in the control group had excessive myxomatous mitral valve leaflets (χ2=7,9; p=0,005). In the ARB group, the expression of type III collagen in the mitral valve leaflets was lower compared to the control group and the expression of fibulin-5 did not differ. Also, in the main group, an increased density of valvular interstitial cells was found, including those expressing TGF-β1 and TGF-β2 compared to the control group. The serum level of TGF-β1 and TGF-β2 was significantly higher in the control group than in the ARB group.Despite the absence of differences in LV ejection fraction between the groups, global longitudinal systolic strain and strain rate were significantly higher in the main group.Conclusion. This is the first study to reveal a positive effect of ARB therapy on myxomatous mitral valve degeneration and LV function due to inhibition of the TGF-β signaling pathway, which opens up potential for pathogenetic therapy in patients with MVP.